Fixation methods for electron microscopy of human and other liver - Wisse, Eddie; Braet, Filip; Duimel, Hans; Vreuls, Celien; Koek, Ger; Olde Damink, Steven W M; van den Broek, Maartje A J; De Geest, Bart; Dejong, Cees H C; Tateno, Chise; Frederik, Peter (World journal of gastroenterology : WJG, 2010)
For an electron microscopic study of the liver, expertise and complicated, time-consuming processing of hepatic tissues and cells is needed. The interpretation of electron microscopy (EM) images requires knowledge of the liver fine structure and experience with the numerous artifacts in fixation, embedding, sectioning, contrast staining and microscopic imaging. Hence, the aim of this paper is to present a detailed summary of different methods for the preparation of hepatic cells and tissue, for the purpose of preserving long-standing expertise and to encourage new investigators and clinicians to include EM studies of liver cells and tissue in their projects.